Eksplorasi Konsep Bangun Ruang dalam Perspektif Etnomatematika pada Rumah Adat Joglo Pencu Kudus - Maulida, Lia Khusna; Ana, Khoirul; Sa’diyah, Halimatus; Zuliana, Eka (Indo-MathEdu Intellectuals Journal, 2026)
Culture is a reflection of the values, traditions, and local wisdom of the community that develop in everyday life, as well as being a medium for the expression of various mathematical and philosophical concepts. This study aims to explore the concept of spatial shapes and the mathematical and philosophical values ​​contained in the Joglo Pencu Traditional House in Kudus Regency through an ethnomathematics perspective. The study uses an exploratory method with an ethnographic approach to reveal the relationship between local cultural elements and geometric forms of spatial shapes. The subject of the study was Mr. P, the caretaker of the Joglo Pencu Traditional House located in the Kudus Kretek Museum area. Data were collected through observation, interviews, and documentation, then analyzed using an interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study show that the structure of the Joglo Pencu Traditional House contains various simple spatial shapes such as cuboids, cubes, rectangular pyramids, cylinders, and spheres, which represent mathematical values. In addition, each spatial shape also implies philosophical values, such as balance, order, and the outlook on life of the Kudus community. This finding confirms that the Joglo Pencu Traditional House contains mathematical and philosophical values ​​that can be analyzed through the geometry of the spatial structure.